Research On Biodegradable Lubricant in Combustion Engine - Hamidon, Muhammad Luqman Haikal; Jumadi, Rozita; Khalid, Amir; Jaat, Norrizam; Salleh, Hamidon; Samion, Syahrullail (Journal of Automotive Powertrain and Transportation Technology, 2023)
Lubricants predominantly used to reduce friction and gain smooth functioning of a vehicle. Biodegradable lubricants are perceived to be alternative to mineral oil lubricants because of their properties and biodegradability. This review paper discusses the effect of biodegradable lubrication in term of emission performance, wear, friction and viscosity effect to the internal combustion engine using multiple types of biodegradable lubrications. Bench wear test was conducted using Yamaha, ET 950 to carry out the effect of the biolubricant in spark ignition (SI) engine. The bench test was conducted under several conditions: pressure, 3.0 MPa; sliding speed, 0.20 m/s; sliding stroke, 80 mm; room temperature, >25°C. The second experiment were conducted with 100 percentage SAE 40, palm oil and palm oil (14%) + castor oil (86%) blend as its crankcase lubricant using four stroke compression ignition (CI) engine. A thermocouple was used to measure the parameters temperature every 5 minutes’ interval with the engine operating for an hour under no load, 2.5 kg, 5 kg, and 7 kg load condition. The emission performance was run using neem oil blends as samples. The brief discussion is made on emission performance, fuel efficiency, viscosity index and coefficient of friction. Also, deduction was made for the temperature of crank case oil, coolant and the exhaust gas.